Effect of hierarchical surface relief grating on light extraction of polymer light-emitting diodes - Lim, Tae-bin; Kim, Kang-Han; Song, Shin Ae; Lim, Sung Nam; Kim, Ki Young; Jeong, Yong-Cheol (Macromolecular research, 2017)
We propose enhanced light extraction of polymer light-emitting diodes (PLEDs) with nano-sized diffractive grating patterns. Various diffractive gratings of hexagonal and quasicrystal patterns were fabricated with photo-addressable azopolymers by light interference lithography. Fabricated patterns were transferred to a glass substrate as a light extraction layer by an imprinting method. We prepared PLED cells having diffractive nano-gratings, and the performance of the PLED cells was systematically investigated in terms of luminous efficiency, external quantum efficiency, and electroluminescence spectrum. Compared to the reference PLED, the quasicrystal PLED cells showed improvements in external quantum efficiency, current efficiency, and power efficiency of 11.54%, 10.93%, and 19.43%, respectively.